AFFECTIVE TEMPERAMENTS IN MENTAL HEALTH AND MOOD DISORDERS - Gostiljac, Marta; Erić, Emilija; Dodić, Sara; Lalović, Nikola; Dunjić-Kostić, Bojana; Prica, Ida; Ivković, Maja; Pantović Stefanović, Maja (Engrami, 2022)
Temperament includes genetic-biological components of behavior that include mood, the way of emotional reaction in terms of speed, intensity, duration and type of reaction, relationship to the environment, and sensitivity to external stimuli.Attempts to classify temperaments date back to the time of Ancient Greece, while the modern concept of temperament is based on the work of Kraepelin and Kretschmer. Hagop Akiskal continued the development of the modern concept of temperament and divided the types of affective temperaments into: depressive, hyperthymic, cyclothymic, irritable and anxious temperament. In a healthy population, temperament represents an important, biological, basis of personality. However, dominant affective temperaments are thought to potentially lie on a continuum between healthy emotional reactivity and affective disorders. Also, dominant affective temperaments in an accentuated form can represent subclinical manifestations of affective disorders, as well as precursors for the emergence of these disorders. Based on strong genetic and neurochemical foundations, affective temperaments have developed and persisted throughout evolution because they carry distinct evolutionary and social advantages. Thus, in addition to pathological, temperamental characteristics can also have an adaptive value.Additional research on understanding of affective disorders as a continuum as opposed to their categorical classification, with respect for the transitional forms they take from mental health to mental disorders, would contribute not only to a better understanding of the emotional life of a man, but also to timely, targeted and better treatment of various psychopathological forms.
Keywords: temperament; affective disorders; continuum; bipolar disorder